The impact of school nutritional campaigns on OFSP adoption and food security among smallholder farming households in Tigray region, Ethiopia. - Kwikiriza, N.; Jogo, W.; Okello, J.J.; Tesfay, H.; Asfaw, F. (2015)
In Ethiopia, the International Potato Center (CIP) and regional partners piloted a 2-year project that promoted production and consumption of vitamin A-rich OFSP as part of diversified diets. The project adopted school-based nutritional campaigns wherein school gardens and school feeding were piloted in 11 schools between 2011 to 2013. The schools served centres for the dissemination of planting material (vines) and transfer of information on benefits of OFSP and its production practices to parents.